Encouraging training skills in the furniture and woodworking industries through an innovative simulation-based approach - Lange, Julia; Majewski, Adam; Wojnowska, Marlena (Global Forest Journal, 2024)
The article presents the results of the project aimed at applying gamification in education. ENCOURAGING SUnRISE ERASMUS+ project builds on the emerging needs of companies in the Wood and Furniture Industry to give employment to young graduated generations (in HE and VET) including: students prepared technically and students motivated to work in this specific sector. To achieve this challenge, the project explored the use of gamification and the Simulation Learning Environment. In particular, ENCOURAGING SUnRISE introduced gamification to the Wood and Furniture Sector training program. The project is a step to trigger modernisation in initial and continuous VET in the sector through gamification and simulation tools. Therefore, the objective of this research was to prepare and investigate the influence of gamification and the Simulation Learning Environment in improving competencies in the furniture and wood sector, as an innovative educational solution. After identifying the needs and challenges, a selection of skills (soft and hard) was made to perform various tasks in the scenario-based simulation game. The quality assessment of the course has been highly rated by students, teachers, and workers As well as the rate of improvement of technical and non-technical knowledge at the end of the course. This creates a chance to respond to needs and opportunities of traditional industries by offering innovative didactic approaches. ENCOURAGING SUnRISE may in a modern and attractive way reinforce the top skills that the most outstanding workers of the sector usually display.